international marketing and the trading system - Kostecki, Michel (Geneva International Trade Centre, 2001)
Study dealing with marketing principles and key managerial decisions facing small and medium-sized enterprises in developing and transition economies, in the light of WTO Agreement and the multilateral trading system - identifies and analyses regulatory problems in export markets; includes case studies illustrating in detail how business firms, in a variety of countries and industries, are affected by regulatory change and how they respond to it.
Introduction -- Chapter 1 The manager in the trading system -- Chapter 2 The business firm and barriers to exporting -- Chapter 3 Marketing management within the international trading system -- Chapter 4 Managing regulatory issues in exporting -- Chapter 5 Business strategy and regulatory change -- Chapter 6 Case studies -- Bibliography -- Index
On top of t.p. International Trade Centre Business and the multilateral trading system, UNCTAD, WTO
Bibliography p.:209-215 Includes index
Keywords: International Trade; INTERNATIONAL TRADE; FOREIGN TRADE; TRADE REGULATION; EXPORTS; PROMOTION; DEVELOPING COUNTRIES